MicroRNA profiling identifies VHL/HIF-2α dependent miR-2355-5p as a key modulator of clear cell Renal cell carcinoma tumor growth - Patric M. Page; Sonia A. Dastous; Patrick O. Richard; Michel Pavic; Tamiko Nishimura; Yasser Riazalhosseini; Nicolas Crapoulet; Mykella Martin; Sandra Turcotte (Cancer Cell International)
Abstract Inactivation of the von Hippel-Lindau (VHL) tumor suppressor gene is one of the first truncal events in clear cell Renal Cell Carcinoma (ccRCC) tumorigenesis. The accumulation of Hypoxia Induced Factor (HIFα) resulting from VHL loss can promote ccRCC tumorigenesis by regulating microRNA (miRNA) expression. Here, we performed miRNA profiling and high-throughput analysis to identify a panel of VHL-dependent miRNAs in ccRCC. Validation of these miRNAs revealed the overexpression of miR-2355-5p in ccRCC cell models and primary tumors. Moreover, we showed a significant increase in circulating miR-2355-5p in plasma from patients with ccRCC. Mechanistically, miR-2355-5p overexpression was confirmed to be HIF-2α dependent. Targeting miR-2355-5p with the CRISPR/Cas9 system not only negatively disrupted the ability of ccRCC cells to stimulate angiogenesis but also decreased cell proliferation and drastically reduced tumor growth in mouse xenograft models. Finally, a miR-2355-5p pulldown assay identified five tumor suppressor genes, ACO1, BTG2, CMTM4, SLIT2, and WDFY2, as potential targets. All five genes were significantly downregulated in ccRCC tumors and mouse xenograft tumors. The results from this research demonstrate the oncogenic ability of miR-2355-5p and shed light on the possible mechanism by which this miRNA controls angiogenesis and tumor growth in VHL-deficient ccRCC.